The Spider Limb Positioner in subscapular system free flaps. (October 2018) - Stevens, Jayne R.; Rosko, Andrew J.; Marchiano, Emily; Haring, Cate; Chinn, Steven B.; Malloy, Kelly M.; Prince, Mark E.; Casper, Keith; Moyer, Jeffrey; Chepeha, Douglas; Stucken, Chaz L.; Spector, Matthew E.
Highlights: The Spider Limb Positioner enabled a two-team approach in all cases. The average operative time was 466 min, and chimeric flaps were used in 38% of cases. A semidecubitus position facilitates exposure without compromising ablative access. Abstract: Background: The subscapular system is a versatile vascular network that can provide multiple flaps for reconstruction of the head and neck. A significant drawback of using the subscapular system is that patient positioning can preclude the use of simultaneous two-team ablative and reconstructive surgery. Herein, we describe a novel use of an upper extremity limb positioner (Spider Limb Positioner) used primarily in orthopedic surgery to facilitate concurrent two-team technique in head and neck surgery. Methods: Using a bean bag and the Spider Limb Positioner for the upper extremity, a semidecubitus position was used for subscapular donor site dissection. Ablative and reconstructive teams worked concurrently in all cases. Results: This technique was utilized 78 times on 73 patients, with chimeric flaps used in 38% of cases. The average operative time was 466 min. Only one patient required repositioning intraoperatively due to a change in the subscapular donor site side. There were no nerve compression injuries or positioning related complications. Conclusion: Scapular and parascapular free flaps are useful tools for reconstruction of the head and neck. In a two-team approach, the use of a semidecubitus position in conjunction with the Spider Limb Positioner facilitates exposure for the reconstructive team without compromising access for the ablative team.